Uncovering the abilities of Agaricus bisporus to degrade plant biomass throughout its life cycle. (4th August 2015) - Patyshakuliyeva, Aleksandrina; Post, Harm; Zhou, Miaomiao; Jurak, Edita; Heck, Albert J. R.; Hildén, Kristiina S.; Kabel, Mirjam A.; Mäkelä, Miia R.; Altelaar, Maarten A. F.; de Vries, Ronald P.
Summary: The economically important edible basidiomycete mushroom A garicus bisporus thrives on decaying plant material in forests and grasslands of North America and Europe. It degrades forest litter and contributes to global carbon recycling, depolymerizing (hemi‐)cellulose and lignin in plant biomass. Relatively little is known about how A . bisporus grows in the controlled environment in commercial production facilities and utilizes its substrate. Using transcriptomics and proteomics, we showed that changes in plant biomass degradation by A . bisporus occur throughout its life cycle. Ligninolytic genes were only highly expressed during the spawning stage day 16. In contrast, (hemi‐)cellulolytic genes were highly expressed at the first flush, whereas low expression was observed at the second flush. The essential role for many highly expressed plant biomass degrading genes was supported by exo‐proteome analysis. Our data also support a model of sequential lignocellulose degradation by wood‐decaying fungi proposed in previous studies, concluding that lignin is degraded at the initial stage of growth in compost and is not modified after the spawning stage. The observed differences in gene expression involved in (hemi‐)cellulose degradation between the first and second flushes could partially explain the reduction in the number of mushrooms during the second flush.